Novel tracking method for the drinking behavior trajectory of pigs - Liu, Chengqi; Ye, Haijian; Wang, Longhe; Lu, Shuhan; Li, Lin (International Journal of Agricultural and Biological Engineering, 2024)
Identifying and tracking the drinking behavior of pigs is of great significance for welfare feeding and piggery management. Research on pigs’ drinking behavior not only needs to indicate whether the snout is in contact with the water fountain, but it also needs to establish whether the pig is drinking water and for how long. To solve target loss and identification errors, a novel method for tracking the drinking behavior of pigs based on L-K Pyramid Optical Flow (L-K OPT), Kernelized Correlation Filters (KCF), and DeepLabCut (DLC) was proposed. First, the feature model of the drinking behavior of a sow was established by L-K OPT. In addition, the water flow vector was used to determine whether the animal drank water and to demonstrate the details of the movements. Then, on the basis of the improved KCF, the relocation model of the sow’s snout was established to resolve the problem of tracking loss in the snout. Finally, the tracking model of piglets’ drinking behavior was established by DLC to build the mapping association between the pig’s snout and the drinking fountain. By using 200 episodes of drinking water videos (30-60 s each) to verify the method proposed in this study, the results are explained that 1) according to the two important drinking water indexes, the Down (−135°, −45°) direction feature and the V2 (>10 pixels) speed feature, the drinking time could be accurate to the frame level, with an error within 30 frames; 2) The overlapping precision (OP) was 95%, the center location error (CLE) was 3 pixels, and the speed was 300 fps, which were all superior to other traditional algorithms; 3) The optimal learning rate was 0.005, and the loss value was 0.0 002. The method proposed in this study realized accurate and automatic monitoring of the drinking behavior of pigs, which could provide reference for other animal behavior monitoring. Keywords: tracking method, drinking behavior trajectory, pigs, L-K optical flow, KCF, DeepLabCut DOI: 10.25165/j.ijabe.20231606.7450 Citation: Liu C Q, Ye H J, Wang L H, Lu S H, Li L. Novel tracking method for the drinking behavior trajectory of pigs. Int J Agric & Biol Eng, 2023; 16(6): 67–76.